Food Fair - The Star (2008)
Universiti Putra Malaysia's Student Representatives Council is Organising a food exhibition-cum-fair at the Food Service Complex (near the Banquet Hall) in its campus in Serdang, Selangor,today at 8am. There will also be a career talk about the food industry at 10am.